Quantitative evaluation of freeze-substitution effects on preservation of nuclear antigens during preparation of biological samples for immunoelectron microscopy - Sobol, Margarita A; Philimonenko, Vlada V; Philimonenko, Anatoly A; Hozák, Pavel (Histochemistry and cell biology, 2012)
Using quantitative evaluation of immuno-gold labeling and antigen content, we evaluated various automated freeze-substitution protocols used in preparation of biological samples for immunoelectron microscopy. Protein extraction from cryoimmobilized cells was identified as a critical point during the freeze-substitution. The loss of antigens (potentially available for subsequent immuno-gold labeling) was not significantly affected by freezing, while the cryosubstitution with an organic solvent caused a significant loss of antigens. While addition of water can improve visibility of some cell structures, it strengthened the negative effect of cryosubstitution on antigen loss by extraction. This was, however, significantly reversed in the presence of 0.5% glutaraldehyde in the substitution medium. Furthermore, we showed that the level of these changes was antigen-dependent. In conclusion, low concentrations of glutaraldehyde can be generally recommended for cryosubstitution rather than the use of pure solvent, but the exact conditions need to be elaborated individually for certain antigens.
Keywords: Freeze Substitution; HeLa Cells; Antigens, Nuclear; glutaraldehyd; Humans; Solvents; mrazová substituce; imunoelektronová mikroskopie; rozpouštědla; Glutaral; antigeny jaderné; HeLa buňky; lidé; Microscopy, Immunoelectron